Nanoindentation on micro pillars for determination of intrinsic hardness and residual stress in coatings deposited on complex geometries - Andrè, B; Hollman, P; Wiklund, U (Tribologia - Finnish Journal of Tribology, 2012)
In this work a procedure to assess the local residual stress in coatings deposited on complex substrate geometries is described. A focused ion beam (FIB) is used to mill structures small enough to relax from residual stress. Nanoindentation is used to measure the change in mechanical properties, most importantly the hardness, in relaxed coating and in as-deposited coating. This change is then related to the residual stress in the coating. This relationship can then be used to calculate the residual stresses, at other positions or at other components, from changes in hardness as measured as before. The procedure is demonstrated on two different PVD coatings; one TiN coating and one nanocomposite TiNiC coating. On a large high speed steel substrate the TiN was measured to a hardness of 28 GPa using conventional techniques. Using this procedure, this could be divided into 23 GPa of intrinsic hardness and an extra 5 GPa induced by the known compressive residual stress of 3.9 GPa. When the same coating was deposited on a thin wire the full procedure allowed the residual stress to be determined to 3.5 GPa in compression.